INDEKS KEPUASAN MASYARAKAT PADA LAYANAN IRIGASI DI WILAYAH KABUPATEN LEBAK TAHUN 2023 - Taufik, Isvan; Marzan, Arlan; Hakim, Zainul; Apriliani, Karvina Budiwati; Hakim, Agus Lukman; Sanjaya, Natta; Yuniar, Siti (Jurnal Kebijakan Pembangunan Daerah, 2024)
The Banten Provincial Government, through the Public Works and Spatial Planning Agency (PUPR), has provided irrigation network services for the community in Banten Province. This study evaluates and assesses community satisfaction with irrigation services in Lebak Regency, organized by the PUPR Agency. The research method used is quantitative descriptive with a saturated sampling technique, involving all Water User Farmer Associations (P3A) or farmer groups that receive irrigation services in Lebak Regency, with 83 respondents from 10 irrigation areas. The study was conducted for 45 days, from November to December 2023. Data were analyzed using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The IPA results showed an overall positive gap, with four questions in quadrant I (high importance and low satisfaction), ten questions in quadrant II (high importance and high satisfaction), nine questions in quadrant III (low importance and low satisfaction), and three questions in quadrant IV (low importance and high satisfaction). The CSI results show a level of public satisfaction of 78.00%, which is included in the "Good" category, according to Permenpan RB. This study provides strategic recommendations to improve the quality of irrigation services and maximize public satisfaction.